Isolated duodenal duplication cyst in a neonate - Riyazhussein Yakoob Hakda; Deepen V Makwana; Ramendra Shukla; Urvish Parikh; Sudhir B Chandna (Wolters Kluwer Medknow Publications, 2022)
Duodenal duplication cysts are a rare subtype of alimentary tract duplications cysts, consisting of 7% of all the duplications. We report a rare case of neonatal duodenal duplication cyst presenting as a palpable abdominal mass and features of gastric outlet obstruction. A 27-day-old male child presented with complaints of icterus, non-bilious vomiting after every feed and right-sided abdominal lump for the last 15 days. A computed tomography scan of the abdomen revealed well-defined peripherally enhancing cystic lesion noted in the subhepatic region extending up to the right lumbar region. On surgical exploration, a cystic mass was found attached to the pyloric part of the stomach along the mesenteric border of the first, second and third part of the duodenum, which was marsupialised, and no communication was found with the duodenum. On histopathological analysis, a duodenal duplication cyst was diagnosed without any heterotopic mucosa. The literature was reviewed and the approach to duodenal duplication cyst in neonates is discussed.